MEMBANGUN INTEGRITAS PELAYANAN DALAM KEPEMIMPINAN PELAYAN GEREJA - Marcella Valeria Zala; Vanny N. Suoth (STAK Reformed Remnant Internasional, 2026)
This study aims to analyze the integrity of church servant leadership and its influence on the faith growth of the congregation at GMIM Moria Darunu by using leadership theory from Peter G. Northouse. This study uses a qualitative research method to understand the phenomenon of church leadership in depth based on the experiences and views of the congregation as well as special ministers. Data collection techniques were carried out through interviews, field observations, and literature studies by reading books and articles related to Christian leadership. The results of the study show that leadership integrity has a very significant influence on the growth of the congregation's faith. Inconsistencies between the teachings and behavior of church ministers create a crisis of trust among the congregation and hinder faith growth, whereas leadership that is of integrity, serves, and sets an example can build trust and encourage the spiritual growth of the congregation.